Shear behavior and failure analysis of a composite T-joint with a cutout. (August 2015) - Li, GC; Xue, P; Luo, G; Yu, ZL; Yang, J; Tu, B
This study investigates the mechanical behavior and the failure of a composite T-joint with a teardrop-shaped cutout under shear loading numerically and experimentally. By establishing a composite finite element model with continuous shell elements and cohesive interface elements, using the progressive damage algorithms, the shear behavior and the failure mechanisms of the composite T-joint are investigated. The change of the load–displacement curve of the T-joint is correlated with the damage development of the T-joint with the cutout, and the typical damage modes are identified. To validate the numerical results, the samples of composite T-joints were manufactured and the experiments were conducted using a universal testing machine. The curve of the load versus deformation and the failure modes are in good agreement with the numerical prediction. In order to further enhance the load-carrying capacity of the composite T-joints with the teardrop-shaped cutout, three reinforcing schemes are proposed and their efficiencies are compared.